The Implementation of Think-Pair-Share (TPS) Strategy in Enhancing al-Mahārah al-Kalām in Grade 8 at MTsN 1 Madiun: Implementasi Strategi Think-Pair-Share dalam Meningkatkan al-Mahārah al-Kalām di Kelas 8 MTsN 1 Madiun - Abdul Hafidz bin Zaid; Zaki Abdul Muhaimin; Akmal Faris Itsarrozan (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
This inquiry makes a deliberate effort to harmonize students' latent instincts and cognitive faculties with the progressive refinement of their Arabic speaking proficiency while confronting pedagogical challenges and uplifting the standards of instruction within the al-Mahārah al-Kalām curriculum. At the heart of this endeavor lies the Think Pair Share (TPS) strategy, a collaborative educational method that encourages individual contemplation and facilitates dialectic engagement and communal reflection. Through such methodological precision, the study aspired to stimulate active participation, deepen comprehension, and enhance students' communicative competencies in the Arabic language. Focusing its gaze on Year Eight students of the State Islamic Junior High School (MTSN) 1 in East Java during the academic year of 2023-2024, the research unfolded through the paradigm of classroom action research (PTK), following the model posited by Kemmis and Taggart. This model, grounded in four distinct stages—planning, observation, implementation, and reflection—allowed the investigation to traverse a meticulously structured path. The process was executed across two cycles: the first cycle centered on "al-Hiwāyah" (aspirations), while the second gravitated towards "mihnah" (professions). Each cycle adhered rigorously to the procedural demands of planning, execution, observation, and subsequent reflection, thus ensuring the validity and reliability of the resultant data. The findings were revealing: there emerged a pronounced enhancement in the quality of instruction, with 75% of the cohort attaining commendable levels of achievement. The TPS strategy enriched the student's grasp of the material and fostered heightened engagement, greater confidence, and an evident fluency in their Arabic speech. In its broader implications, this study underscores the efficacy of the TPS method in furthering both the pedagogical quality and the linguistic proficiency of students within the al-Mahārah al-Kalām framework for Year Eight at MTSN 1  Madiun. Keywords: Learning Outcome, al-Mahārah al-Kalām, Think Pair Share (TPS)